Crescimento, desenvolvimento e produtividade de mandioca em função da adubação e manejo de plantas daninhas - Cardoso, Paula de Souza (2021)
The increase in the world population, which may exceed 10 billion in 2050, will require low-cost and easy production. As a result, cassava (Manihot esculenta Crantz) was chosen by the UN as the 21st century crop. The objective of this study was to verify the influence of fertilization and the period of weed control on the growth and development of the cassava crop, and to determine a morphological indicator to identify the beginning of starch accumulation (BSA) and the yield in cassava cultivars. Two studies were carried out, the first was conducted in cassava field in Ibarama and Santa Maria in Rio Grande do Sul in 2018/2019 representing the management practices carried out by farmers such as the fertilizer amount and weed control. The second study was carried out in Santa Maria in the 2018/2019 and 2019/2020 growing season in order to determine the number of leaves at the beginning of starch accumulation and the yield of seven registered and unregistered cassava cultivars. The yield of tuberous roots when fertilizing and controlling weeds was 43.5 Mg ha-¹, reaching 80% of the yield potential, besides of the 50% increase the accumulation in shoot dry matter. BSA can be identified by the morphological indicator number of leaves, ranging from 24 leaves in IAC 576 cultivar to 33 leaves in Fepagro RS13 cultivar.